An integrated decision support system for the Mediterranean forests - Costas Freitas, M.B. (2018)
tMediterranean forests contain a relevant biological diversity and are relevant for local economy. However,they are subject to various risks, particularly the risk of forest fires. This turns the critical decisions offorest managers, affecting both the long-term future of the forest and daily activities, to be difficult. Tosimulate decisions, and help managers and policy makers, a decision support system, which integrates thebiological, environmental and economic management perspectives of agricultural and forest areas, wasdeveloped and considers the activities existing in the territory. The decision support system considers thecharacteristics of the biophysical units that comprise the territorial study area, production technologiesand conservation of agro-forestry goods and preferences of managers or stakeholders. The proposedapproach was applied in a pilot Forest Intervention Zone (FIZ) located within the Algarve region innerland. The results show that the decision support system proposed is an important tool for managing theterritory and for implementing the manager’s decisions.